Agriculture of Prykarpattya (1939-1991 years) in the historiograhy - Roman Vеprіv (Cхід, 2013)
The article analyzes the status of the problems studied in the Soviet foreign and modern Ukrainian history, policy of the Soviet government and the Communist Partyimposition of socialist methods of management in the agricultural sector of western village at different stages, a new course to overcome totalitarian thinking, highlighted the features of its implementation in Ivano-Frankivsk.